Photographic composition : a visual guide - Zakia, Richard D. (Focal, 2011)
However amazing the subject or technically excellent the photography, the single biggest factor in deciding whether a photograph is good or bad is how well it is composed. Photographic Composition Visualized offers a unique take on this fundamental issue by offering instruction in a visual format - the book is laid out in a unique spread format of a beautiful image on one page, with an in-depth break down of why the rule of composition works in the image, but also how a photographer can apply it to their own photography. Inspirational, instructive, and, most importantly, visually stunning and.